Impaired ATG16L-Dependent Autophagy Promotes Renal Interstitial Fibrosis in Chronic Renal Graft Dysfunction Through Inducing EndMT by NF-κB Signal Pathway - Gui, Zeping; Suo, Chuanjian; Wang, Zijie; Zheng, Ming; Fei, Shuang; Chen, Hao; Sun, Li; Han, Zhijian; Tao, Jun; Ju, Xiaobin; Yang, Haiwei; Gu, Min; et al. (Frontiers in Immunology, 2021)
Chronic renal graft dysfunction (CAD) is caused by multiple factors, including glomerular sclerosis, inflammation, interstitial fibrosis and tubular atrophy (IF/TA). However, the most prominent elements of CAD are IF/TA. Our studies have confirmed that endothelial-mesenchymal transition (EndMT) is an important source to allograft IF/TA. The characteristic of EndMT is the loss of endothelial marker and the acquisition of mesenchymal or fibroblastic phenotypes. Autophagy is an intracellular degradation pathway that is regulated by autophagy-related proteins and plays a vital role in many fibrotic conditions. However, whether or not autophagy contributes to fibrosis of renal allograft and how such mechanism occurs still remains unclear. Autophagy related 16 like gene (ATG16L) is a critical autophagy-related gene (ARG) necessary for autophagosome formation. Here, we first analyzed kidney transplant patient tissues from Gene Expression Omnibus (GEO) datasets and 60 transplant patients from our center. Recipients with stable kidney function were defined as non-CAD group and all patients in CAD group were histopathologically diagnosed with CAD. Results showed that ATG16L, as one significant differential ARG, was less expressed in CAD group compared to the non-CAD group. Furthermore, we found there were less autophagosomes and autolysosomes in transplanted kidneys of CAD patients, and downregulation of autophagy is a poor prognostic factor. In vitro, we found out that the knockdown of ATG16L enhanced the process of EndMT in human renal glomerular endothelial cells (HRGECs). In vivo, the changes of EndMT and autophagic flux were then detected in rat renal transplant models of CAD. We demonstrated the occurrence of EndMT, and indicated that abundance of ATG16L was accompanied by the dynamic autophagic flux change along different stages of kidney transplantation. Mechanistically, knockdown of ATG16L, specifically in endothelial cells, reduced of NF-κB degradation and excreted inflammatory cytokines (IL-1β, IL-6 and TNF-α), which could facilitate EndMT. In conclusion, ATG16L-dependent autophagic flux causing by transplant showed progressive loss increase over time. Inflammatory cytokines from this process promoted EndMT, thereby leading to progression of CAD. ATG16L served as a negative regulator of EndMT and development of renal graft fibrosis, and autophagy can be explored as a potential therapeutic target for chronic renal graft dysfunction.